Students and graduates with autism: perceptions of support when preparing for transition from university to work. Issue 4 (8th August 2021) - Pesonen, Henri V.; Waltz, Mitzi; Fabri, Marc; Lahdelma, Minja; Syurina, Elena V.
ABSTRACT: Despite the steps taken to improve support in universities, many students and graduates with autism face a substantial employment gap when completing university as compared to any other student group with disabilities. The literature shows that often students with autism do not have appropriate support to prepare them for entering the workforce. Therefore, it is imperative that this under-researched topic be studied. Utilising a participatory approach, in this article, we sought to investigate perceptions of students and graduates with autism about the employment support they received when preparing for university-to-work transition. The study involved semi-structured interviews with 30 university students and graduates with autism from Finland, France, the Netherlands, and the UK. Data were analysed using an inductive content analysis approach. Findings indicate that organisational enablers consisting of career-focused support and internships and practicums facilitated preparation for employment. Supportive and caring relationships emerged as forms of support that included mentors, committed and caring academics, and family members. Further, the findings indicated the aspiration for individualisation that consists of improving work and academic support, and awareness and understanding. These findings have also important practical implications.